HIV prevention programme cascades: insights from HIV programme monitoring for female sex workers in Kenya. (22nd July 2019) - Bhattacharjee, Parinita; Musyoki, Helgar K; Becker, Marissa; Musimbi, Janet; Kaosa, Shem; Kioko, Japheth; Mishra, Sharmistha; Isac, Shajy K; Moses, Stephen; Blanchard, James F
Abstract: Introduction: HIV prevention cascades have emerged as a programme management and monitoring tool that outlines the sequential steps of an HIV prevention programme. We describe the application of an HIV combination prevention programme cascade framework to monitor and improve HIV prevention interventions for female sex workers (FSWs) in Kenya. Methods: Two data sources were analysed: (1) annual programme outcome surveys conducted using a polling booth survey methodology in 2017 among 4393 FSWs, and (2) routine programme monitoring data collected by (a) 92 implementing partners between July 2017 and June 2018, and (b) Learning Site in Mombasa (2014 to 2015) and Nairobi (2013). We present national, sub‐national and implementing partner level cascades. Results: At the national level, the population size estimates for FSW were 133, 675 while the programme coverage targets were 174, 073. Programme targets as denominator, during the period 2017 to 2018, 156, 220 (90%) FSWs received peer education and contact, 148, 713 (85%) received condoms and 83, 053 (48%) received condoms as per their estimated need. At the outcome level, 92% of FSWs used condoms at the last sex with their client but 73% reported consistent condom use. Although 96% of FSWs had ever tested for HIV, 85% had tested in the last three months. Seventy‐nine per cent of the HIV‐positive FSWs were enrolled in HIV care, 73% were currently enrolled on antiretroviral therapy (ART) and 52% had attended an ART clinic in the last month. In the last six months, 48% of the FSWs had experienced police violence but 24% received violence support. National and sub‐national level cascades showed proportions of FSWs lost at each step of programme implementation and variability in programme achievement. Hotspot and sub‐population level cascades, presented as examples, demonstrate development and use of these cascades at the implementation level. Conclusions: HIV prevention programme cascades, drawing on multiple data sources to provide an understanding of gaps in programme outputs and outcomes, can provide powerful information for monitoring and improving HIV prevention programmes for FSWs at all levels of implementation and decision‐making. Complexity of prevention programmes and the paucity of consistent data can pose a challenge to development of these cascades.